1984
DOI: 10.1021/ac00268a018
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene-mediated enzyme electrode for amperometric determination of glucose

Abstract: An amperometric enzyme electrode tor the analysis of glucose Is described. The electrode uses a substituted ferrlcinlum Ion as a mediator of electron transfer between Immobilized glucose oxidase and a graphite electrode. A linear current response, proportional to the glucose concentration over a range commonly found In diabetic blood samples (1-30 mM), is observed. Data are presented on the Influence of oxygen, pH, and temperature upon the electrode. Results with clinical plasma and whole blood samples show go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
674
1
10

Year Published

1992
1992
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,596 publications
(714 citation statements)
references
References 14 publications
16
674
1
10
Order By: Relevance
“…50% and occurs over several hours exposure to brain tissue (Garguilo and Michael, 1994;Hu et al, 1994). Although previous in vitro studies have shown that Pt/PPD/GOx sensors are virtually free from both protein and lipid fouling (Lowry and O'Neill, 1994) we carried out an additional in vitro conditioning of the sensors prior to implantation (see Section 2.4), similar to the preconditioning procedure used by Hill and coworkers to improve the stability of ferrocene-mediated glucose biosensors (Cass et al, 1984). The mean baseline current recorded with preconditioned Pt/PPD/ GOx sensors implanted in the striatum of freely-moving animals showed no significant variation (p\ 0.88, twoway ANOVA; n= 6) over a successive 5 day period from day 0 (ca.…”
Section: Stability Of Biosensor In 6i6omentioning
confidence: 99%
“…50% and occurs over several hours exposure to brain tissue (Garguilo and Michael, 1994;Hu et al, 1994). Although previous in vitro studies have shown that Pt/PPD/GOx sensors are virtually free from both protein and lipid fouling (Lowry and O'Neill, 1994) we carried out an additional in vitro conditioning of the sensors prior to implantation (see Section 2.4), similar to the preconditioning procedure used by Hill and coworkers to improve the stability of ferrocene-mediated glucose biosensors (Cass et al, 1984). The mean baseline current recorded with preconditioned Pt/PPD/ GOx sensors implanted in the striatum of freely-moving animals showed no significant variation (p\ 0.88, twoway ANOVA; n= 6) over a successive 5 day period from day 0 (ca.…”
Section: Stability Of Biosensor In 6i6omentioning
confidence: 99%
“…66 Ferrocene-modified polypyrrole was subsequently used to immobilize glucose oxidase. 6 7 -68 Highly flexible ferrocene-modified siloxanes and polyethylene oxides were also used as mediators, carrying electrons between glucose oxidase and other enzymes and high surface area carbon pastes that adsorb the enzyme and the redox polymer. 6 9 -7 4 In most of these redox-polymer systems, the polymers, often of low molecular weight (20, …”
Section: Electrical Wiring Of Enzymesmentioning
confidence: 99%
“…Many efforts have been made to improve the selectivity of carbon based electrochemical sensors, mainly through their modification with redox mediators (Cass et al, 1984;Frew and Hill, 1987).…”
Section: Introductionmentioning
confidence: 99%